Bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II) anchored onto chloromethylated polystyrene for the biomimetic oxidative coupling of 2-aminophenol to 2-aminophenoxazine-3-one - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
2-(alpha-Hydroxyethyl)benzimidazole (Hhebmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This polymer-anchored chelating resin reacts with cupric acetate in presence of Hhebmz to give polymer-anchored copper(II) complex PS-[Cu(hebmz)(2)]. Elemental analyses, FT-IR, electronic, scanning electron micrographs (SEM) and TGA-DTA pattern have been used to characterize the complex. Oxidative coupling of 2-aminophenol (OAP) to 2-aminophenoxazine-3-one (APX) catalyzed by PS-[Cu(hebmz)(2)] in presence of air at 70 degrees C in DMF gave 62% substrate conversion over a period of 8 h. Kinetics of the above reaction indicated that the rate of oxidative coupling of OAP has a first order dependence with respect to substrate, catalyst and air pressure (dissolved O-2) concentrations in the range of conditions evaluated. Based on these observations, a plausible mechanism for the above reaction has been proposed. From, the study on the effect of temperature on the rates of oxidative coupling, an activation energy 34.2 kcal/degree mole was evaluated from Arrhenius plot of -ln rate versus 1/T. Enthalpy, entropy and free energy were calculated using standard thermodynamic equations for the above reaction. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-aminophenol; 2-aminophenoxazine-3-one; bis(2-[alpha-hydroxyethyl]benzimidazolato)copper(II); chloromethylated polystyrene; oxidative coupling

Synthesis, characterization and catalytic potentials of polymer anchored copper(II), oxovanadium(IV) and dioxomolybdenum(VI) complexes of 2-(alpha-hydroxymethyl)benzimidazole - Maurya, Mannar R.; Sikarwar, S.; Joseph, Trissa; Manikandan, Palanichamy; Halligudi, Shivappa B. (Reactive & Functional Polymers, 2005)
{2-(alpha-Hydroxymethyl)benzimidazole (Hhmbmz) has been covalently anchored to chloromethylated polystyrene cross-linked with 5% divinylbenzene. This chelating resin reacts with cupric acetate, vanadyl sulphate and [MoO(2)-(acac)(2)] (Hacac = acetylacetone) in presence of Hhmbmz to give complexes PS-[Cu(hmbmz)(2)], PS-[VO(hmbmz)(2)] and PS-[MoO(2)(hmbmz)(2)] (where
Keywords: 2-(alpha-hydroxymethyl)benzimidazole; oxidation of styrene and ethyl benzene; oxidative bromination of salicylaldehyde; polymer anchored-complexes

Oxovanadium(IV) complex of 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene for oxidation of benzoin - Maurya, Mannar R.; Sikarwar, Sweta; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Vanadyl sulphate reacts with 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene (PS-Hhebmz) cross-linked with 5% divinyl benzene to give PS-[VO(hebmZ)(2)]. Characterisation of the catalyst was carried out by IR, electronic and EPR spectroscopic studies, thermogravimetry, scanning electron micrographs and elemental analyses. Catalytic potential of the complex was tested for the oxidation of benzoin using tert-butyl hydroperoxide (TBHP) as an oxidant in methanol where benzil, methylbenzoate, benzoic acid and dimethylacetal were obtained as products. Various parameters such as different solvents and concentration of the substrate as well as oxidant have been taken into consideration for the maximum oxidation of the benzoin. Under optimised reaction conditions, a maximum of 98.9% conversion of the benzoin was achieved after 6 h of reaction time where selectivity of the obtained reaction products varied in the order: methylbenzoate (48.5%) > benzil (19.5%) > dimethylacetal (17.1%) > benzoic acid (11.5%). Neat complex was also prepared to compare its catalytic property with polymer-anchored one. EPR spectra of neat and polymer anchored catalyst are characteristics of V(IV) complexes with typical axial pattern and possible square pyramidal geometry. The identical EPR spectral patterns of both freshly prepared and recovered anchored catalysts indicate that the complex is stable and the coordination environment is retained at the end of the catalytic reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2-(alpha-hydroxyethyl)benzimidazole; oxidation of benzoin; polymer-anchored complex; Polystyrene; vanadium(IV) complex

Polymer supported vanadium and molybdenum complexes as potential catalysts for the oxidation and oxidative bromination of organic substrates - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (Dalton Transactions, 2006)
{The Schiff base (H(2)fsal-ohyba) derived from 3-formylsalicylic acid and o-hydroxybenzylamine has been covalently bonded to chloromethylated polystyrene cross-linked with 5% divinylbenzene ( abbreviated as PS-H(2)fsal-ohyba, I). Treatment of [
Keywords: Bile acids; bis-steroids; hybrids; Peptides; polyamines; saponins; steroidal conjugates; synthetic ionophores

Synthesis and characterisation of polymer-anchored oxidovanadium(IV) complexes and their use for the oxidation of styrene and cumene - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (European Journal of Inorganic Chemistry, 2007)
{The Schiff bases H(2)fsal-ea (I), H(2)fsal-pa (II) and H(2)fsal-amp (III), derived from 3-formylsalicylic acid and 2-aminoethanol, 3-aminopropanol and 2-amino-2-methylpropanol, respectively, have been connected, by means of covalent bonds, to chloromethylated polystyrene cross-linked with 5% divinylbenzene. On treatment with [
Keywords: dissolution rate; mass transfer coefficient; particle size distribution; polydisperse solid; reactive liquid